Exploring the Learning of Language Through Global Dance and Music: a Theoretical Analysis - Norah Banafi (International Conference on Education and Language (ICEL), 2014)
This research paper explores theories behind Total Physical Response (T.P.R) methods and psychology by associating them with music in order to examine the role of listening to music and dancing in language learning. This research utilises the five pillars of Zumba (music, dance, the power of now, enjoyment, and relaxing) that may create an environment for motivating language fluency learning and investigates whether these pillars have the potential for making Zumba, a global phenomenon in teaching languages. Studies depicting how listening to music facilitates foreign language learning will be outlined. This is a personal form of ethnographic research requiring the participant researcher to investigate the role of music and dance in increasing learner motivation learning the English language.